Níveis séricos de vitamina "A" em pré-escolares de um bairro pobre de Manaus - AM - Marinho, Helyde Albuquerque; Castro, Janete Seixas de; Burini, Roberto Carlos (Acta Amazonica, 1989)
The nutritional status of vitamim A was studied in 240 children of both sexes between the ages of three and seven years who lived in a poor residential area of Manaus (Amazonas), Brazil. Biochemical analyses of serum retinol and β-carotene were carried out and the dietary intake was determined by means of questionnaires. Thirty - six percent and 65% of the children had serum retinol an β-caroten levels, respectively, below the normal levels, which, according to the ICNND criteria, suggests a public heath problem. The man dietaru a intake dietary vitamin A intake was only 62,6% of the US Recommended Dietary Allowance (RDA).